Crítica social e quebras de expectativas em Parasita: estilo, narrativa e gestalt na criação de tensões no filme de Bong Joon-ho - Lucas Tunes Barbosa (2022)
It is undeniable the cultural relevance that the film Parasite (2019), by Bong Joon-ho, conquered worldwide after awards as important as the Palme d'Or at the Cannes Festival and the Oscar for Best Film from the Academy of Motion Picture Arts and Sciences of the United States. Audience reactions were in the sense of considering Parasite as a comic film, as well as a tense, surprising and socially critical movie. The text seeks to identify which aspects of the filmic style of Parasite corroborate these audience perceptions and how they can relate to each other. From the narrative point of view, the definitions of Hollywood International style and erotetic narrative, both concepts by Noel Carroll, were taken into account, as well as the effects, on the spectator, of narrative strategies such as the creation of suspense, surprise and curiosity, and expectations created by these strategies in general. From the graphic/pictorial point of view, we consider the concepts of animage, by Gaudreault and Marion, and Rudolf Arnheim's Gestalt, as well as the effects of using previews such as storyboards in the production of the film. Finally, the analysis of the film itself highlighted the question and answer structure, both in the scenes and in the narrative as a whole, as well as their relationships with the film themes subjects; it also highlighted the relationships between narrative tensions and power dynamics between characters, as well as the role of mise-en-scène, visual composition and sequentiality in the construction of these tensions; as well as the thematic and moral implications of maintaining and breaking narrative and stylistic expectations.